How to maintain and expand the star wars film franchise in Indonesia - Soeharli, Kevin Ardhana; Wibowo, Satya Aditya (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The objectives of this research are to find out the primary reasons Indonesian customers watch the movies. To advise a proper marketing strategy for future Star Wars films so the revenue of the film franchise will grow optimally. In other words, to increase the number of Star Wars films audience. To find out the optimal promotional channel for the Star Wars film franchise to expand its customer base in Indonesia. To develop an implementation plan for the proposed marketing strategy. This research used primary and secondary data. The primary data are from quantitative and qualitative research, whereas the secondary data are from various internet sources. The conclusion shows that the future of the Star Wars film franchise is deeply connected and dependent on its fanbase due to the nature of the Star Wars brand embedding nostalgia within its fans, young and old. Time and time again, the fans have been responsible for some of the best marketing ploys in the industry, like Star Wars Day, “May the fourth be with you,” which was organically created by the fans to appreciate and celebrate the Star Wars films. Star Wars fans continue to create demands for Star Wars films and merchandise. They also organically create new fans by spreading their joy and hobby in Star Wars. Indonesian customers watch movies to be entertained but a major reason is so that they are up to date with the current trend.